2006
DOI: 10.1128/jb.188.6.2163-2172.2006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of [FeFe] Hydrogenase Maturation in an Escherichia coli Biosynthetic System

Abstract: H 2 metabolism in microorganisms requires the catalytic activity of hydrogenases, a specialized group of metalloproteins (29,38,51 (8,10,12,28,37,42,45). In contrast, characterization of [FeFe] hydrogenase maturation has been limited by a lack of knowledge of the proteins functioning in the biosynthesis of the catalytic H cluster. Recently, we identified two genes in Chlamydomonas reinhardtii, hydEF and hydG, which encode proteins required for [FeFe] hydrogenase activity by functioning in H cluster biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
312
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(319 citation statements)
references
References 53 publications
5
312
0
2
Order By: Relevance
“…HydA from Clostridium pasteurianum was cloned as described previously [5] modified for the presence of an N-terminal 6x-histidine tag. Constructs were confirmed by DNA sequencing.…”
Section: Cloning and Heterologous Expression Of Hyd Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…HydA from Clostridium pasteurianum was cloned as described previously [5] modified for the presence of an N-terminal 6x-histidine tag. Constructs were confirmed by DNA sequencing.…”
Section: Cloning and Heterologous Expression Of Hyd Proteinsmentioning
confidence: 99%
“…Recent studies involving the analysis of mutants of Chlamydomonas reinhardtii defective in hydrogen production have revealed that products of the hydEF and hydG genes are required for the accumulation of active [FeFe] hydrogenase, and that hydE, hydF, and hydG are common to all organisms in which active [FeFe] hydrogenases are found [4]. Further studies have shown that the coexpression in Escherichia coli of HydE, HydF, and HydG from Clostridium acetobutylicum with the HydA [FeFe] hydrogenase protein from a variety of microbial sources enables the formation of active [FeFe] hydrogenases [5]. Genome annotation indicates that HydE and HydG are members of the radical Sadenosylmethionine (AdoMet) enzyme family, and that HydF is likely to be a GTPase [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant expression of the hydrogenase CpHydA from Clostridium perfringens SM09 [22] was performed in E. coli 30 Rosetta2(DE3) as previously described [31] upon transformation of the competent cells with plasmid pECPF2655, obtained by ligating the entire coding sequence of CPF_2655 into the empty expression vector pECr1 [23,24] between NdeI and XhoI sites. After the induction, cells were incubated over night under pure argon flow to maintain anaerobic conditions in a water bath at 30°C.…”
Section: Recombinant Expression and Purificationmentioning
confidence: 99%
“…In this work, a novel [FeFe]-hydrogenase CpHydA (encoded by CPF_2655 gene) from a Clostridium perfringens strain newly isolated in a pilot plant with high hydrogen productivity [21][22][23] was immobilized by adsorption on stationary TiO2 electrodes. The heterologous expression in E. coli was achieved thanks to a previously established system [23,24] and it allowed to obtain a pure and active protein in good yields. Anatase TiO2 was used because of its ability to bind hydrogenases [9] with a favourable orientation for electron transfer by simple adsorption; this is possibly due to a major The resulting hydrogen producing bioelectrode was validated by chronoamperometric experiments and tested for production of hydrogen gas by quantitative measurement in gas chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…This moiety is comprised of the proximal [4Fe-4S] cluster and a connected dithiolate-, CO-, and CN-containing 2Fe center which serves as the active site (21). In bacteria, trichomonads, and possibly algae, synthesis of the H-cluster depends on the specialized biogenesis factors (termed HydEFG) which are not conserved in other eukaryotes (25)(26)(27)(28). Hence, it seems unlikely that eukaryotic Nar1 proteins contain an H-type catalytic center, rendering the function of the C-terminal cysteine residues unclear.…”
mentioning
confidence: 99%